Evaluation of futsal motor index based on TGMD-3 in the learning to train phase: a sport science approach - Putra, Aditya Diana; Hariadi, Imam; Fadhli, Nurrul Riyad (Universitas Sriwijaya, 2026)
Research Problems: In Indonesia, data on the motor skills index of futsal players aged 9–12 years is still very limited. This is also reflected at the Kuantanamo Futsal Academy, which does not yet have a measurable motor skills evaluation system based on sports science. The lack of standardized data is a major obstacle in designing effective, long-term training programs. Research Objective: This study aims to evaluate the gross motor skills of futsal players at the Kuantanamo Futsal Academy as a basis for planning training programs. Methods: This study used a non-experimental research design with a quantitative descriptive approach. The sampling technique used was total sampling, involving 20 students from the Kuantanamo Futsal Academy. The instruments used were TGMD-3 for locomotor skills and control objects. The data collection technique used a test technique, and this study used a quantitative descriptive data analysis technique based on percentages to interpret the results of gross motor skill measurements. Results: The results showed that the locomotor score had an average value of 42 (SD=4; Min=35; Max=48), while the control object score had an average value of 47 (SD=4; Min=39; Max=58). The GMQ assessment showed an average of 22 (SD=3; Min=16; Max=28), which was close to the average value in the TGMD-3 norm, where most players were in the very superior motor index category with a score of 95%, with a tendency for control object values to be higher than locomotor values. The balance and agility components showed low to moderate values, indicating the need to improve the basic motor training program. These findings confirm that although control object abilities are relatively good, imbalances in locomotor, balance, and agility aspects can hinder long-term performance if not immediately intervened. Conclusion: In conclusion, the motor training of futsal players at this stage needs to be directed more systematically to support the development of performance, especially in playing futsal optimally. In closing, further research is recommended to test the effectiveness of FMS-based or sport science training programs so that skill development programs can be designed to be more targeted, adaptive to the needs of participants, and contribute to improving the effectiveness of long-term training.